2015
DOI: 10.1007/s10552-015-0702-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of exogenous hormones and the risk of breast cancer: results from self-reported survey data with validity assessment

Abstract: Purpose Main aim was to estimate the association between use of exogenous hormones and breast cancer (BC) risk in a large population-based survey, and to assess the representativeness and overall validity of the data. Methods The survey 'Women's Health and Use of Hormones' was conducted in Finland in 2009, including 7,000 BC cases and 20,000 matched population controls. Conditional logistic regression was used to estimate odds ratios and their 95 % confidence interval. For validation, exposure prevalences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 39 publications
1
33
0
6
Order By: Relevance
“…29 Currently, T-shaped copper IUDs are the most commonly-used type among Chinese women. 6 A survey about estrogen and breast cancer conducted in Finland found a positive association between breast cancer risk and previous hormonal IUD use in post-menopausal women (OR 1.48; 95% CI, 1.10–1.99), 30 while a cohort study of 66,661 Chinese women in Shanghai found that more than 14 years’ exposure to IUDs may be a protective factor for breast cancer (HR 0.80; 95% CI, 0.62–1.02). 31 We found that at least 20 years’ exposure to IUD was associated with decreased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…29 Currently, T-shaped copper IUDs are the most commonly-used type among Chinese women. 6 A survey about estrogen and breast cancer conducted in Finland found a positive association between breast cancer risk and previous hormonal IUD use in post-menopausal women (OR 1.48; 95% CI, 1.10–1.99), 30 while a cohort study of 66,661 Chinese women in Shanghai found that more than 14 years’ exposure to IUDs may be a protective factor for breast cancer (HR 0.80; 95% CI, 0.62–1.02). 31 We found that at least 20 years’ exposure to IUD was associated with decreased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Women's Health and Use of Hormones (WHH) survey was conducted as a self-administered questionnaire in 2009. The WHH survey was initially developed to collect information on exogenous hormone use, but it has also covered a wide variety of other lifestyle factors [21]. BC cases were identified from the Finnish Cancer Registry; women aged 18-60 years with BC diagnosed between 1st January 2000 and 31st December 2007 were considered eligible.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Out of the 12,251 women to whom the survey was sent and to whom we were able to link the required data, 8364 (68%) responded. Details of the survey and data collection have been described previously [21,22].…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mørch et al found that more than years of use was associated with increased cancer risk, and the risk lasted up to 10 years after cessation of use(9). In our analysis stratified on duration we could not reproduce this finding.Among previous studies, a Finnish case-control study of 9537 breast cancer cases and 21 598 controls adjusted for age at menarche, smoking, alcohol use, BMI, and family history of breast cancer and found a positive association between ever use of LNG-IUS and breast cancer in postmenopausal women (aged 51-64), while for premenopausal women no association was observed(35). The authors mentioned the possible presence of selection bias, as some practitioners, at least in Finland (this is also the case in Norway), have regarded the LNG-IUS as a preferable option for women with an increased risk of breast cancer.…”
mentioning
confidence: 96%